Modelling of weather characteristics and wind power density in Elazig-Turkey - Akpinar, Ebru Kavak; Akpinar, S. (Sila Science, 2010)
Dynamic thermal simulation has been used for some years to model the performance of ion thermal systems, to enable better understanding of their behavior than is possible by simpler methods. Simulation of buildings and energy systems requires appropriate weather data. In this work, the weather conditions and wind power density of in Elazig-Turkey over a period of 12 years (1994-2005) are studied and modeled. The study involves temperature, relative humidity, wind speed, pressure, solar radiation, Sunshine duration and wind power density. A regression analysis is carried out by using the linear regression technique to model the weather parameters. The models developed can be used in any study related to weather and its effect on the environment and energy.
Keywords: Wind; Solar radiation; Sunshine duration; Weather parameters; Wind speed; Wind power